SWOT ANALYSIS IN PRODUCTIVE MANAGEMENT OF CASH WAQF FUNDING AT MICRO WAQF BANK OF ALMUNA BERKAH MANDIRI KRAPYAK YOGYAKARTA - Kholis, Muhammad Nur; Harmoyo, Dwi (STAI Asy-Syukriyyah, 2024)
The role of institutions in managing cash waqf provided security guarantees and wider investment of funds. Here, the question arises of how to manage cash waqf funding at Bank Wakaf Mikro (BWM) using the SWOT approach. This research aimed to determine the strength factors, weakness factors, opportunity factors, and threat factors in the implementation of cash waqf fund management by BWM Almuna Berkah Mandiri Krapyak. This research was a type of field research using qualitative descriptive methods. Data collection techniques were observation, interviews, and documentation. Meanwhile, the data analysis technique was obtained from various sources through triangulation and carried out continuously until saturation. The results of this research could conclude that the strength factors in managing cash waqf funding at BWM Almuna Berkah Mandiri were good human resources and infrastructure. Meanwhile, the weak factor was that social media management was not running well, so promoting customer products was less than optimal. The opportunity factor was the ease of technology, where customers would find it easy to get information from the Micro Waqf Bank. Finally, the threat factor in managing cash waqf funding was the existence of customers who were in trouble, where customers needed to make installment payments at the agreed time.